(untitled) (Research, Society and Development, 2022)
The present study aimed to show how the Nacional Program of Access and Quality Improvement in Primary Health Care (PMAQ-AB) results can help Primary Health Care (PHC) managers to plan and make better decisions regard healthcare access and quality. It is a cross-sectional study based on data from 3rd Cycle of PMAQ-AB of a city of São Paulo, including Self-evaluation, External Evaluation and Indicators of Performance. Based on the results, managers should consider these items when make decisions and plans: Participation, Social Control and Patient Satisfaction, Workers Valuing, care indicators of health conditions, exams and services’ supply. We did not found data from Self-Evaluation in PHC Management which flags fragilities in health management. The PMAQ-AB seems to be an important tool do ground pathways for manager planning and decisions making and its interruption represents an important loss for the strengthening and consolidation of SUS public policies aimed at Primary Care, in addition to the discontinuity of a consistent Program with good subsidies for evaluation and research.